(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
This article explores the status of the Uzbek language as the national language of Uzbekistan and its significance in the country’s literature. It provides an overview of the historical development of the Uzbek language and its role in shaping the cultural identity of Uzbekistan. The article discusses prominent representatives of Uzbek literature, highlighting their contributions to the preservation and promotion of the Uzbek language. It also examines the efforts undertaken by Uzbekistan to elevate the status of the Uzbek language and foster its growth and recognition.